1992
DOI: 10.1093/aje/136.7.873
|View full text |Cite
|
Sign up to set email alerts
|

Psychoactive Drugs and the Risk of Injurious Motor Vehicle Crashes in Elderly Drivers

Abstract: To determine whether commonly used psychoactive drugs increase the risk of involvement in motor vehicle crashes for drivers > or = 65 years of age, the authors conducted a retrospective cohort study. Data were obtained from computerized files from the Tennessee Medicaid program, driver's license files, and police reports of injurious crashes. Cohort members were Medicaid enrollees 65-84 years of age who had a valid driver's license during the study period 1984-1988 and who met other criteria designed to exclud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
227
1
13

Year Published

1995
1995
2013
2013

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 372 publications
(252 citation statements)
references
References 0 publications
11
227
1
13
Order By: Relevance
“…Higher blood concentrations of benzodiazepines, either used for hypnotic [31] or anxiolytic purposes [34], produce significantly higher traffic accident risks when compared to the risks observed when administering the recommended dose. Although not found in elderly [30], recent epidemiological evidence confirmed that the blood concentration of benzodiazepines was significantly related to impairment in apprehended drivers [35].…”
Section: Discussionmentioning
confidence: 99%
“…Higher blood concentrations of benzodiazepines, either used for hypnotic [31] or anxiolytic purposes [34], produce significantly higher traffic accident risks when compared to the risks observed when administering the recommended dose. Although not found in elderly [30], recent epidemiological evidence confirmed that the blood concentration of benzodiazepines was significantly related to impairment in apprehended drivers [35].…”
Section: Discussionmentioning
confidence: 99%
“…the responsibility for the accident) into account. 19 This may also explain the seemingly opposite results from studies in elderly showing sometimes significantly increased risks when using benzodiazepine hypnotics 12,15 whereas other studies do not. 13,17 In these studies, benzodiazepines with a long half-life significantly increased traffic accident risks, whereas those with a short halflife did not.…”
Section: Epidemiological Evidencementioning
confidence: 96%
“…The authors did not find an association between crash risk and benzodiazepine or sedating antihistamines among this group, although they acknowledged that the sample size (234 drivers) might have been too small for significance. Ray, Fought, and Decker (1992) also studied crash risk for drivers aged 65 years or older using data from the Tennessee Medicaid program. With this larger sample (16,262 drivers), they found an association between presence of benzodiazepines or tricyclic antidepressants and crash risk.…”
Section: Field Datamentioning
confidence: 99%